Corporate governance and firms cash holding in Malaysia - Azira Hanani Ab. Rahman; Siti Fariha Muhamad (2013)
Corporate governance code has being introduced in many countries recently in order to improve minority shareholders right protection as well as the firms’ transparency. The corporate governance system is also being used to make sure the management of the company run the company in the best interest of all stakeholders especially the shareholders. Some managers may have their own interest of holding excessive cash and overspending it on unnecessary and unprofitable projects Thus, this study investigates the relationship between cash holding and corporate governance among listed firms in Malaysia. This study measures corporate governance by looking at the internal perspective as the primary mechanism which is the board of directors. The objective of this study is to identify the relationship of shareholders’ power on cash holdings. The data of 512 public listed companies in Malaysia is obtained from DataStream as well as from firms’ annual report for the year 2009. From this study, it is found that there is a positive relationship between Board Independence and the level of cash holding for the sample firms. This finding is consistent with shareholder power hypothesis which indicate that firm with shareholder who have more effective control rights tend to allow manager to build up more cash reserve